United Republic of Tanzania - Public Expenditure and Financial Accountability Review for FY07 - World Bank (Washington, DC, 2012)
Tanzania has carried out an annual Public Expenditure Review (PER) process since 1997/98 with interrelated twin objectives of supporting the budget process as well as undertaking an external review of fiscal developments. The Public Expenditure and Financial Accountability Review (PEFAR) aims to integrating two diagnostic exercises to facilitate a comprehensive assessment of Public Financial Management (PFM). This report presents the findings of the external review of fiscal developments. The overall purpose of the PEFAR is to provide Government of Tanzania (GoT) and development partners with a comprehensive, integrated and candid assessment of Tanzania's key fiduciary risks as reflected in GoT's resource allocation, resource management and control, resource utilization and accountability processes, and to make recommendations for improving the PFM framework, institutional performance and capacity building.